Survey of economics - Tucker, Irvin B. (Mason, Ohio : Cengage Learning Asia Pte Ltd, 2016)
Presents the basics of economics in the context of real-world situations to show you how economic issues play out at national and international levels. This edition addresses intriguing topics in today's economics, such as the federal deficit and national debt, income levels and fair pay for females, social networking sites, and gasoline prices.
Part I. introduction to economics -- Part II. the microeconomy -- Part III. the macroeconomy and fiscal policy -- Part IV. money, banking, and monetary policy -- Part V. the international economy.
Includes index.
Keywords: ECONOMICS